2017
DOI: 10.1016/j.jssc.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of RE6Cd23T (RE=La–Gd; T=Sn, Sb, Pb, and Bi)

Abstract: Synthetic methods and structural characterization are reported for 11 novel ternary compounds with the general formula RE 6 Cd 23 T (RE = La-Gd; T = Sn, Sb, Pb, and Bi). Their crystal structures, as revealed by single-crystal and powder X-ray diffraction, are of the cubic Zr 6 Zn 23 Si structure type (cF120, Fm  3m, Z = 4), a filled version of the Th 6 Mn 23 system. No Cdcontaining rare-earth metal binaries are known to form with this structure, but the inclusion of small amounts of a third element allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(34 citation statements)
references
References 24 publications
(41 reference statements)
3
30
1
Order By: Relevance
“…As was the case with our previous RE 6 Cd 23 T work (Desroches & Bobev, 2017), the experimental diffraction pattern was easily indexed and the intensities matched up well with the simulations generated from the subsequent single-crystal work. The data were used for phaseidentification only.…”
Section: Synthesis and Crystallizationsupporting
confidence: 78%
See 4 more Smart Citations
“…As was the case with our previous RE 6 Cd 23 T work (Desroches & Bobev, 2017), the experimental diffraction pattern was easily indexed and the intensities matched up well with the simulations generated from the subsequent single-crystal work. The data were used for phaseidentification only.…”
Section: Synthesis and Crystallizationsupporting
confidence: 78%
“…It should be noted that in our previous RE 6 Cd 23 T study (Desroches & Bobev, 2017) we observed that the identity of the interstitial atom T had a considerable effect on the phase purity. Specifically, it was found that heavy-atom interstitials gave better yields than their lighter counterparts.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations